Revision of the huntsman spider genus Micrommata Latreille, 1804 (Sparassidae: Sparassinae) - Jäger, Peter (Zootaxa, 2023)
The genus Micrommata Latreille, 1804 is revised and two new species are described: Micrommata biggi spec. nov. (male, female; Türkiye, Armenia, Iran, Turkmenistan), and M. diesenhoff spec. nov. (male, female; Sierra Leone). Micrommata aragonensis Urones, 2004 is synonymised with M. formosa Pavesi, 1878. All known species are redescribed and illustrated, and an identification key for males and females is provided for all true Micrommata species. A distribution map is provided for all species. M. formosa is for the first time recorded from Portugal, M. ligurina (C.L. Koch, 1845) from Morocco, the latter species having been introduced into United Kingdom and Germany. Micrommata darlingi Pocock, 1901 (female; Zimbabwe) is considered misplaced and probably related to the genus Eusparassus Simon, 1903. Functional copulatory mechanics are briefly discussed using µ-CT scans.